Damage evolution and avalanche characteristics of concrete under salt-freezing action by acoustic emission - Yunfeng Zhao; Minghui Chen; Xiang Jiang; Xuepeng Cao; Binbin Qin (Developments in the Built Environment, 2025)
Concrete structures in saline-alkali areas will suffer from salt freezing and cause diseases. In this paper, experiments of concrete deterioration under the coupling action of sulfate attack and freeze-thaw cycles were carried out. The avalanche characteristics of acoustic emission (AE) signals generated during concrete failure were analyzed statistically by avalanche dynamics theory, and compared with traditional AE analysis methods. The results show that with the increase of cycle times, the proportion of shear cracks in the failure process of concrete specimens gradually increases, and the AE b-value increases. the energy distribution exponent, amplitude distribution exponent, and duration distribution exponent of concrete specimens gradually increase, while the correlation exponent between amplitude and absolute energy decreases, and the correlation exponent between duration and amplitude fluctuates within a certain range. The distribution exponent of waiting time shows robustness. Avalanche exponents can be applied to the quantitative characterization of concrete damage under the salt-freezing action.